HIGHER LINGUISTIC EDUCATION IN RUSSIA: PROBLEMS OF SINOLOGISTS TRAINING - Tatyana L. Guruleva; Andrey V. Makarov (Высшее образование в России)
The article studies organizational and pedagogical problems of sinologists training at institutions of higher education in Russia. The definition of higher sinological linguistic education is given, also the main educational programs of higher professional education in this sphere are determined, an analysis of the main organizational and pedagogical problems of sinologists training is made in the article. The ways to solve the above-mentioned problems on the federal and regional levels are offered.